PENGARUH TERAPI BERMAIN PUZZLE TERHADAP TINGKAT KECEMASAN ANAK USIA PRASEKOLAH PADA SAAT HOSPITALISASI DI RUANG ANAK RS BHAYANGKARA SARTIKA ASIH - Helena, Denni Fransiska; Alvianda, Vinny Widi (Jurnal Ilmu Kesehatan Immanuel, 2019)
Hospitalization is a condition that the child requires hospitalized whether it is planned or not. At the time of hospitalization, children experience anxiety and fear, anxiety due to separation, and losing control of themselves and also their usual play assignments because play is an important aspect in children. Play therapy in the hospital can minimize the occurrence of developmental problems, provide a sense of security, and also as therapeutic activity that provides opportunities for children to express themselves, and one of the examples is play puzzle therapy. The purpose of this research is to determine the influence of play puzzle therapy on the level of anxiety during hospitalization in the Pediatrics Room at Bhayangkara Sartika Asih Hospital. The research design used is pre-experimental design with one group pre and posttest design with non-probability. The retrieval sampling method is purposive sampling as many as 30 respondents who experienced mild to severe level of anxiety during hospitalization at pediatrics room in Bhayangkara Sartika Asih Hospital. Data is collected by observing the level of anxiety before and after given play puzzle therapy, and then analyze using the Wilcoxon test. The results of this research indicated that p value of 0,000 <α (0.05) meaning that there was an influence of play puzzle therapy on the children level of anxiety at the time of hospitalization. The recommendation of the research results is as a reference for nurses in the management of play puzzle techniques in overcoming the children’s anxiety of preschool ages.